Are Accrual Earnings Management and Real Earnings Management Related to Total Risk and Idiosyncratic Risk? - Rohmat Kunto Wijoyo; Amrie Firmansyah (Riset Akuntansi dan Keuangan Indonesia, 2021)
This study aims to determine the association between accrual earnings management and real earnings management with total risk and idiosyncratic risk in Indonesia. This study approach employs quantitative methods. The secondary data in this study were sourced from financial reports and share prices of textile and garment sub-sector companies listed on the Indonesia Stock Exchange from 2015 up to 2019 obtained from www.idx.co.id, www.idnfinancials.com, and www.finance.yahoo.com. Based on purposive sampling, the number of samples in this study amounted to 75 observations. Hypothesis testing employed in this study is multiple regression analysis for panel data. This study suggests that accrual earnings management is negatively associated with total risk and idiosyncratic risk, but real earnings management is positively associated with total risk and idiosyncratic risk. Earnings accrual management carried out by managers for efficiency is not a risky action. This study indicates that the Financial Services Authority needs to improve policies related to investor protection in Indonesia. In addition, investors should consider information about the company's ability to generate operating cash flow and stock price trends in recent years compared to information on high earnings in making investment decisions.